2022
DOI: 10.1097/mpg.0000000000003551
|View full text |Cite
|
Sign up to set email alerts
|

Progression to Anti-TNF Treatment in Very Early Onset Inflammatory Bowel Disease Patients

Abstract: Objectives: Limited data are currently available regarding anti-tumor necrosis factor (TNF) use and outcomes in very early onset inflammatory bowel disease (VEOIBD) patients. We aimed to assess the long-term outcomes and time to progression to anti-TNF treatment in VEOIBD patients. Methods: We retrospectively reviewed IBD patients diagnosed under 6 years of age, between January 2005 and December 2019, from the British-Columbia (BC) Pediatric IBD database. Demographic data, disease characteristics, disease loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A meta-analysis by the ESPGHAN-IBD working group suggests that a higher dose per kilogram of body weight may be appropriate in younger IBD patients, as they often have lower trough levels in the early phase of therapy induction [ 51 ]. Indeed, a retrospective British study demonstrated that children with very early onset IBD received the increased dose of 10 mg/kg body weight [ 40 ]. The remission rate in these patients was 62%; otherwise, the course of very young children with IBD treated with biologics appears to be similar to that of older patients [ 40 , 41 ].…”
Section: Therapeutic Drug Monitoring To Optimize the Treatment Strate...mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis by the ESPGHAN-IBD working group suggests that a higher dose per kilogram of body weight may be appropriate in younger IBD patients, as they often have lower trough levels in the early phase of therapy induction [ 51 ]. Indeed, a retrospective British study demonstrated that children with very early onset IBD received the increased dose of 10 mg/kg body weight [ 40 ]. The remission rate in these patients was 62%; otherwise, the course of very young children with IBD treated with biologics appears to be similar to that of older patients [ 40 , 41 ].…”
Section: Therapeutic Drug Monitoring To Optimize the Treatment Strate...mentioning
confidence: 99%
“…Indeed, a retrospective British study demonstrated that children with very early onset IBD received the increased dose of 10 mg/kg body weight [ 40 ]. The remission rate in these patients was 62%; otherwise, the course of very young children with IBD treated with biologics appears to be similar to that of older patients [ 40 , 41 ]. In particular, studies in pediatric patients with ulcerative colitis and Crohn’s disease have shown that higher infliximab trough levels after induction predict remission one year after infliximab administration [ 52 , 53 ] (see also Table 2 ).…”
Section: Therapeutic Drug Monitoring To Optimize the Treatment Strate...mentioning
confidence: 99%
“…The long-term outcomes and time to progression to anti-TNF treatment in 89 very early onset-IBD patients were reviewed between January 2005 and December 2019 in a study from Canada (30). Median age at diagnosis was 3.8 years, 45.3% had Crohn disease, and 62.8% were males.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%